The Implementation of Information and Communication Technology in Teaching Mahārah Al-Kalām at MTsN Pacitan - Biqi Asshafah Zain (Faculty of Education and Teacher Training, 2026)
This study examines the implementation of Information and Communication Technology (ICT) in teaching mahārah al-kalām (Arabic speaking skills) at MTsN Pacitan. The problem addressed is the limited oral communication proficiency among students despite conventional grammar-based instruction. A qualitative descriptive design was adopted to investigate how ICT tools such as learning management systems, video-conferencing platforms, and multimedia-based speaking tasks support student engagement and oral language development. Data were collected through classroom observations, interviews, and document analysis, and were analyzed thematically. The findings indicate that ICT promotes greater interaction, authentic communication practice, and learner confidence, while also supporting differentiated instruction. However, challenges remain in teacher digital competence, infrastructure readiness, and structured task design. The study concludes that ICT integration provides a viable innovation for strengthening Arabic speaking pedagogy in Islamic secondary schools and highlights the need for sustained professional development and system support. These results contribute to ongoing efforts to modernize Arabic language teaching in Indonesia.